Cardiac function in dogs with chronic Chagas cardiomyopathy undergoing autologous stem cell transplantation into the coronary arteries - Sousa, Marios G.; Paulino-Junior, Daniel [UNESP]; Pascon, João P. E. [UNESP]; Pereira-Neto, Gláucia B. [UNESP]; Carareto, Roberta; Champion, Tatiana [UNESP]; Camacho, Aparecido A. [UNESP] (My University, 2011)
This study assessed the effects of a single intracoronary injection of autologous stem cells on the cardiac function of dogs with Chagas cardiomyopathy. Bone-marrow-derived stem cells were delivered into the right and left coronary arteries of 5 mature dogs with mildly compromised cardiac function due to chronic Chagas cardiomyopathy. Blood pressure and electrocardiographic and echocardiographic parameters were recorded at monthly intervals for 6 mo in the 3 dogs that survived. Although no changes were observed in the electrocardiogram and blood pressure, there was a significant increase in peak velocity of aortic flow 3 mo after stem cell transplantation. Pre-ejection period, isovolumic relaxation time, and the Tei index of myocardial performance were reduced significantly 4 mo after the procedure. All significant changes persisted to the end of the study. The results suggest that the transplantation of autologous bone-marrow-derived stem cells into the coronary arteries of dogs with Chagas cardiomyopathy may have a beneficial effect but the small number of dogs studied was a limitation.